Evaluation of natural vinegars as growth promoter in the black tiger shrimp penaeus monodon. - Calzada, Rey Jamisolamin de la (2020.)
Primarily, this study, composed of three experiments was undertaken to determine the effects of incorporating coconut sap vinegar (CSV), sugar cane vinegar (SCV) and combination of coconut sap vinegar (CSV) and sugar cane vinegar (CSV) on the growth and feed efficiency performance of Penaeus monodon. In the first experiment, 360 post larva shrimps (average initial weight of 0.01g) were randomly distributed into 12 50-L plastic containers to investigate the effect of acidifying the diet of black tiger shrimp P. monodon on its growth and feed efficiency by supplementing coconut sap vinegar (CSV) or sugar cane vinegar (SCV) or their 1 : 1 combination. Four experimental diets, namely, control diet, 2% CSV, 2% SCV and 2% CSV+SCV were fed to groups of shrimps. After 90 days, all shrimps fed with diets containing 25 CSV,2% SCV AND 2% CSV+SCV vinegar exhibited significantly higher final average body weight (FABW), weight gain (WG), feed intake, specific growth rate (SGR), and better feed conversion ratio (FCR) than those fed the control diet (P>0.05). Attractability tests showed that the CSV and CSV+SCV diets attracted significantly the highest percentage of shrimps after 10 min of feed placement. survival rate was not significantly different among the treatments. The results demonstrated that the vinegars tested could be used as growth enhancers in shrimp. The shrimps fed diets supplemented 2% combination of CSV and SCV had the best growth (88.46% increase in weight gain) and best FCR (20% decrease) compared to the shrimp fed the control diet. The shrimps fed diet supplemented 2% combination of coconut sap and sugar cane vinegars also attracted the most percentage of shrimps. In the second experiment, 540 post larva shrimps (average initial weight of 0.08g were randomly distributed into 18 50-L plastic containers to determine the effects of various levels of the combined dietary coconut sap vinegar (CSV) and sugar cane vinegar (SCV) (1 : 1 w/w) in the diet of black tiger shrimp P. monodon on growth and feed efficiency. Five experimental diets, namely, control diet 1%, 2%, 3%, 4% and 5% CSV+SCV (1 : 1 w/w) were fed to groups of shrimps. After 60 days, all shrimps fed with diets containing vinegar except for the 1% inclusion level exhibited significantly higher final average body weight (FABW), weight gain (WG), feed intake, specific growth rate (SGR), and better feed conversion ratio (FCR) than those fed the control diet (P<0.05). Survival rate was not significantly different among the treatments. In the third experiment, shrimps were fed a diet which was supplemented with 0 (no vinegar) and 2% combination of coconut sap and sugar cane vinegars (CSV=SCV, 1 :1 w/w) for 15 days and RNA was extracted and sequenced for transcriptome profiling. Then the KEGG pathways were analyzed to elucidate the mechanism involved in growth of P. monodon. Through the KEGG pathway analysis, pentose phosphate pathway, amino sugar and nucleotide sugar metabolism, glycolysis/ gluconeogenesis, fatty acid metabolisms, glycosaminoglycan degradation and glycosphingolipid biosynthesis pathway are the primary mechanisms involved. Results of the experiments showed that feeding P. monodon post larvae with diets supplemented with the vinegars increased the attractability of feeds, improved growth performance and feed utilization. The combination diet (CSV+SCV) exhibited the highest FABW, WG, FI, SGR and lowest FCR. Also, the diet containing CSV alone or 1 : 1 CSV+SCV were very effective in attracting the most proportion of shrimps among other dietary treatments. In terms of improving growth performance and feed utilization of P. monodon postlarvae, a 2%-5% supplementation of CSV+SCV (1 : 1 w/w/) vinegars in the diet proved to be effective, with a 2% inclusion level considered the optimum in terms of practicability. This study provides valuable information about the effect of vinegars on p. monodon. The genes and pathways, which were identified in the current study, could help to reveal the molecular mechanisms responsible for the effect of vinegars on metabolism in P. monodon.
Dissertation - Graduate Faculty - Institute of Aquaculture, College of Fisheries and Ocean SciencesUniversity of the Philippines Visayas.
Keywords: Natural vinegars; Black tiger shrimp; Penaeus monodon; Coconut sap vinegar; Sugar cane vinegar; Organic acids; KEGG pathways; Transcriptome analysis